Pelaksanaan Kampanye Pemilihan Bupati Dan Wakil - Hasibuan, Ulpa Sari; Harahap, Ikhwanuddin; Hasiah, Hasiah (Jurnal El-Thawalib, 2021)
This thesis is entitled "Implementation of the Regent and Deputy Regent Election Campaign During the Covid-19 Pandemic In South Labuhan Batu Regency". The problem in this thesis is to determine the implementation of the regent and deputy regent election campaign during the covid-19 pandemic in South Labuhan Batu Regency and a review of siyasa fiqh about campaigns during the epidemic.The type of research used by the researcher is descriptive qualitative research, the data used are primary and secondary data, the method of collecting data is observation, interviews, and through library research.Based on the results of the research that the implementation of the election campaign for the regent and deputy regent in South Labuhan Batu Regency was successfully carried out by following the health protocol regulations, but there were still many who violated the government's lack of firmness to impose sanctions so that in its implementation BAWASLU issued 4 warning letters and dissolved the campaign.While in the fiqh siyasah review, the implementation of the campaign during the covid period is theoretically appropriate according to the siyasah fiqh because the implementation of this campaign still pays attention to the safety of the ummah Although the implementation is not appropriate because many of the campaign participants violate the regulations (health protocols)